Prisoners should not be left behind in HCV research and policies - Moazen, Babak; Stöver, Heino; Dolan, Kate; Jahn, Albrecht; Neuhann, Florian (Harm reduction journal, 2020)
With a worldwide prevalence of 15.4%, hepatitis C virus (HCV) has been estimated to be the most prevalent major infectious disease in prisons. The exceptionally high prevalence of HCV in prisons is attributable to common risk behaviors including sharing contaminated tattooing equipment and drug paraphernalia, as well as lack of HCV control interventions including needle and syringe programs. Despite the importance of attention to prisoners as a highly at-risk population to acquire and transmit HCV, the number of HCV research and policy documents ignoring prisoners is increasing. Highlighting this issue, the present manuscript discusses how excluding prisoners from HCV-related research and policies will jeopardize the global HCV elimination goals set forth by the global community.
Gesehen am 31.03.2021